Lemma 46.3.14. Let $A$ be a ring. Let $0 \to \underline{M} \to G \to L \to 0$ be a short exact sequence of module-valued functors on $\textit{Alg}_ A$ with $L$ linearly adequate. Then $G$ is adequate.

**Proof.**
We first point out that for any flat $A$-algebra map $B \to B'$ the map $G(B) \otimes _ B B' \to G(B')$ is an isomorphism. Namely, this holds for $\underline{M}$ and $L$, see Lemma 46.3.5 and hence follows for $G$ by the five lemma. In particular, by Lemma 46.3.7 we see that $G(B) = \bigoplus _{k \in \mathbf{Z}} G(B)^{(k)}$ for any graded $A$-algebra $B$.

Choose an exact sequence $0 \to L \to \underline{A^{\oplus n}} \to \underline{A^{\oplus m}}$. Suppose that the map $A^{\oplus n} \to A^{\oplus m}$ is given by the $m \times n$-matrix $(a_{ij})$. Consider the graded $A$-algebra $B = A[x_1, \ldots , x_ n]/(\sum a_{ij}x_ j)$. The element $(x_1, \ldots , x_ n) \in \underline{A^{\oplus n}}(B)$ maps to zero in $\underline{A^{\oplus m}}(B)$ hence is the image of a unique element $\xi \in L(B)$. Observe that $\xi \in L(B)^{(1)}$. The map

defines an isomorphism of functors. The reason is that $f$ is determined by the images $c_ i = f(x_ i) \in C$ which have to satisfy the relations $\sum a_{ij}c_ j = 0$. And $L(C)$ is the set of $n$-tuples $(c_1, \ldots , c_ n)$ satisfying the relations $\sum a_{ij} c_ j = 0$.

Since the value of each of the functors $\underline{M}$, $G$, $L$ on $B$ is a direct sum of its weight spaces (by the lemma mentioned above) exactness of $0 \to \underline{M} \to G \to L \to 0$ implies the sequence $0 \to \underline{M}(B)^{(1)} \to G(B)^{(1)} \to L(B)^{(1)} \to 0$ is exact. Thus we may choose an element $\theta \in G(B)^{(1)}$ mapping to $\xi $.

Consider the graded $A$-algebra

There are three graded $A$-algebra homomorphisms $p_1, p_2, m : B \to C$ defined by the rules

We will show that the element

is zero. First, $\tau $ maps to zero in $L(C)$ by a direct calculation. Hence $\tau $ is an element of $\underline{M}(C)$. Moreover, since $m$, $p_1$, $p_2$ are graded algebra maps we see that $\tau \in G(C)^{(1)}$ and since $\underline{M} \subset G$ we conclude

We may write uniquely $\tau = \underline{M}(p_1)(\tau _1) + \underline{M}(p_2)(\tau _2)$ with $\tau _ i \in M \otimes _ A B_1 = \underline{M}(B)^{(1)}$ because $C_1 = p_1(B_1) \oplus p_2(B_1)$. Consider the ring map $q_1 : C \to B$ defined by $x_ i \mapsto x_ i$ and $y_ i \mapsto 0$. Then $\underline{M}(q_1)(\tau ) = \underline{M}(q_1)(\underline{M}(p_1)(\tau _1) + \underline{M}(p_2)(\tau _2)) = \tau _1$. On the other hand, because $q_1 \circ m = q_1 \circ p_1$ we see that $G(q_1)(\tau ) = - G(q_1 \circ p_2)(\tau )$. Since $q_1 \circ p_2$ factors as $B \to A \to B$ we see that $G(q_1 \circ p_2)(\tau )$ is in $G(B)^{(0)}$, see Lemma 46.3.7. Hence $\tau _1 = 0$ because it is in $G(B)^{(0)} \cap \underline{M}(B)^{(1)} \subset G(B)^{(0)} \cap G(B)^{(1)} = 0$. Similarly $\tau _2 = 0$, whence $\tau = 0$.

Since $\theta \in G(B)$ we obtain a transformation of functors

by mapping $f : B \to C$ to $G(f)(\theta )$. Since $\theta $ is a lift of $\xi $ the map $\psi $ is a right inverse of $G \to L$. In terms of $\psi $ the statements proved above have the following meaning: $\tau = 0$ means that $\psi $ is additive and $\theta \in G(B)^{(1)}$ implies that for any $A$-algebra $D$ we have $\psi (ul) = u\psi (l)$ in $G(D)$ for $l \in L(D)$ and $u \in D^*$ a unit. This implies that $\psi $ is a morphism of module-valued functors, see Lemma 46.3.13. Clearly this implies that $G \cong \underline{M} \oplus L$ and we win. $\square$

## Post a comment

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

## Comments (0)